การศึกษาการจัดทำหลักสูตรสถานศึกษาขั้นพื้นฐาน ในโรงเรียนสังกัดสำนักการศึกษาเมืองพัทยา - วรรณี ศิริวัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To study the state and problems of basic curriculum construction in schools under the Education Department, Muang Pattaya Authority. The population were schools under the Education Department, Muang Pattaya Authority. Bywhich data were gathered from Muang Pattaya Academic committee members, school board members, and schools academic promotion and curriculum administration committee members, also academic strands committee members. The research instruments employed were structured interview forms, questionnaire, and document analysis forms. Data were analyzed by using content analysis and frequency. The results were as follows : 1. The preparation stage : Both Muang Pattaya Authority and schools organized meetings, and workshops for school personnel in order to create the awareness. Workshops, study tours were organized so as to materials provided for curriculum guidelines preparation, instructional activities employed, measurement and evaluation criterias, also school curriculum strands. School academic promotion and curriculum administration committee was organized so as to academic strands committee. Management of information system was organized in each school to provide data on students, personnel, buildings and grounds, economics, social, local wisdoms, and local community resources. Action plans and work schedules were formulated for plan implementation. 2. The curriculum organization stage : School vision, mission and goals, includings students desirable characteristics were set upon analyzing data on students, personnel, buildings and grounds, economic, social, and community, and they will be approved by school administrator, school academic assistance, teachers and school board members. Curriculum structure, yearly and semestery learning outcomes were set up by teachers within each academic strands. Subject syllabuses were prepared, so as to learning units and instructional plans. Students development activities were designed to composed of counseling activities and student activities which composed of boy scout, girl scout, and other activities which students can choose upon their interest. 3. The curriculum implementation stage : Personnel were prepared through meetings, workshops, and study tours. Teachers were assigned according to their experiences, class schedule and other supporting services were also prepared. Supervision was conducted through instructional observations and classroom visits. Public relation activities were conducted through many kind of medias in order to create the mutual understanding to the community. Integrating techique was emphasized upon instructional activities whereby measurement and evaluation techniques were emphasized on authentic assessment through portfolio and actual performance.